TAMAN KANAK-KANAK AL-IRSYAD AL-ISLAMIYYAH KABUPATEN KETAPANG - Fairuzita, Suci; Kalsum, Emilya; Caesariadi, Tri Wibowo (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2026)
Early childhood (0-5 years) is a golden age period in children's growth and development. During this period, developmental delays can have an impact on children's motor, language, social-emotional skills, as well as their ability to interact and follow rules. Kindergarten plays an important role in providing appropriate stimulation to prevent these delays. Al-Irsyad Al-Islamiyyah Kindergarten, located in Ketapang Regency, West Kalimantan, is a formal educational institution that instills Islamic values with the main objective of “instilling a love of the Qur'an”. The design of this kindergarten uses the architectural sensory aspect approach, which stimulates five main senses: vision (Visual), auditory (Auditory), tactility (Tactility), olfactory (Olfactory) and taste (Haptic). The design results in a building mass with a building facade dominated by yellow color that gives a cheerful impression. There are two floors, the first floor functions as a learning area with the application of the center learning method which includes religion, social, science, preparation, and physical-motor classes and the second floor is used for supporting spaces for kindergarten activities and a meeting hall. The design of the kindergarten aims to encourage the involvement of children's senses in recognizing to love the Qur'an and make the values of the Qur'an as a guideline in the kindergarten design and is expected to provide a variety of learning environments that support children's development in accordance with the objectives of Al-Irsyad Al- Islamiyyah Kindergarten Ketapang Regency.